Probiotic Supplementation’s Efficacy and Safety in Preventing Healthcare-Associated Infections: A Systematic Review and Meta-Analysis - Satria, Fauzi; Widyawati, Tri; Dwi Jalma, Monica (Talenta Publisher, 2024)
Background: Infections that people may get while seeking treatment in health facilities are known as healthcare-associated infections (HAIs). The application of probiotics represents a forefront approach in ongoing research and development for the prevention of HAIs. Probiotics' effectiveness has been the subject of several prior research, although the findings have not always been consistent. Objectives: This research aims to determine the efficacy and safety of probiotic supplementation in lowering HAIs when compared to a placebo. Methods: The PRISMA 2020 guidelines were followed in this investigation. Using the keywords